Hanseníase: comparação entre testes rápidos com antígeno PGL-I em amostras de sangue-total e soro - Grassi, Adriano Badotti (2008)
Objectives: This study compared two leprosy rapid tests detecting (1) IgM against PGL-I (ML-Flow test, KIT, Amsterdam, Netherlands) or (2) IgM, IgG and IgA against PGL-I (ML-ICA, Yonsei University, South Korea). Methods: Whole blood and serum from untreated multibacillary (MB; n=50) and paucibacillary (PB; n=48) leprosy patients (Reference Center for Diagnosis and Treatment, Goiania, central Brazil), MB household contacts (HHC; n=35) and healthy endemic controls (EC; n=50) were tested. Leprosy patients were classified by dermato-neurological evaluation, bacillary index (BI) and histopathology. Median age was 29 years, 39.9% males. MB patients had BB-BL-LL leprosy (median BI=2.0), PB patients had TT-BT leprosy. Results: (1) Using sera, ML Flow positivity of MB patients was comparable to ML-ICA positivity. (2) For ML-Flow tests, the positivity was comparable with whole blood and serum. (3) Among PB leprosy ML- flow positiviy was comparable for whole blood and serum but it was higher than the ML-ICA seropositivity in whole blood and serum. (4) Among MB leprosy patients positivity of ML Flow test in serum and whole blood was comparable to the positivity of ML-ICA in serum. Conclusion: ML-Flow test is more field applicable than ML-ICA since high positivity was observed among MB patients using whole-bood.